Typologies and features of play in mobile games for mental wellbeing - Reay, E; Ma, M; Krzywinska, T; Pavarini, G; Hugh-Jones, S; Mankee-Williams, A; Belinskiy, A; Bhui, K (SAGE Publications, 2023)
Background: The smartphone market is saturated with apps and games purporting to promote mental wellness. There has been a significant number of studies assessing the impact of these digital interventions.